A Fucosylated Glycopeptide as a Candidate Biomarker for Early Diagnosis of NASH Hepatocellular Carcinoma Using a Stepped HCD Method and PRM Evaluation - Lin, Yu; Zhang, Jie; Arroyo, Ana; Singal, Amit G.; Parikh, Neehar D.; Lubman, David M. (Frontiers in Oncology, 2022)
Aberrant specific N-glycosylation, especially the increase in fucosylation on specific peptide sites of serum proteins have been investigated as potential markers for diagnosis of nonalcoholic steatohepatitis (NASH)-related HCC. We have combined a workflow involving broad scale marker discovery in serum followed by targeted marker evaluation of these fucosylated glycopeptides. This workflow involved an LC-Stepped HCD-DDA-MS/MS method coupled with offline peptide fractionation for large-scale identification of N-glycopeptides directly from pooled serum samples (each n=10) as well as differential determination of N-glycosylation changes between disease states. We then evaluated the fucosylation level of the glycoprotein ceruloplasmin among 62 patient samples (35 cirrhosis, 27 early-stage NASH HCC) by LC-Stepped HCD-PRM-MS/MS to quantitatively analyze 18 targeted glycopeptides. Of these targets, we found the ratio of fucosylation of three tri-antennary glycopeptides from site N762, involving N762_HexNAc(5)Hex(6)Fuc(1)NeuAc(3) (P=0.04), N762_ HexNAc(5)Hex(6)Fuc(2)NeuAc(3) (P=0.04), and site N138_ HexNAc(5)Hex(6)Fuc(1)NeuAc(3) (P=0.02), increased significantly from cirrhosis to early HCC. These three fucosylation ratios of tri-antennary glycopeptides in CERU would be potential biomarkers for further validation in a larger sample set and could be promising candidates for early detection of NASH HCC.